2003
DOI: 10.4269/ajtmh.2003.69.331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Post-Treatment Reactions to Ivermectin/Albendazole for Wuchereria Bancrofti in a Region Co-Endemic for Mansonella Perstans

Abstract: Post-treatment reactions to single-dose ivermectin (200 g/kg) and albendazole (400 mg) were studied in a filarial endemic region of Mali. The prevalence of Wuchereria bancrofti in this region was 48.3% (69 of 143), and coinfection with Mansonella perstans was common (30 of 40, 75%). Microfilarial levels of M. perstans correlated positively with age (P ‫ס‬ 0.006) and with W. bancrofti microfilarial levels (P ‫ס‬ 0.006). Forty individuals (28 infected and 12 uninfected) were treated, with mild post-treatment rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
0
19
1
Order By: Relevance
“…All filaria-infected individuals were treated with single-dose ivermectin plus albendazole; at 8 months posttreatment, the monocytes from the W. bancrofti-infected patients were isolated and compared with those pretreatment. With a larger sample size, we have previously (12) reported that circulating filarial antigen levels at 8 months following treatment were significantly lower than those pretreatment (n ϭ 26; P ϭ 0.010). In addition, a significant decrease in W. bancrofti MF counts was reported (n ϭ 15; P ϭ 0.002); however, in the same study, it was shown that M. perstans counts did not change significantly (n ϭ 29; P ϭ 0.58) following treatment (12) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All filaria-infected individuals were treated with single-dose ivermectin plus albendazole; at 8 months posttreatment, the monocytes from the W. bancrofti-infected patients were isolated and compared with those pretreatment. With a larger sample size, we have previously (12) reported that circulating filarial antigen levels at 8 months following treatment were significantly lower than those pretreatment (n ϭ 26; P ϭ 0.010). In addition, a significant decrease in W. bancrofti MF counts was reported (n ϭ 15; P ϭ 0.002); however, in the same study, it was shown that M. perstans counts did not change significantly (n ϭ 29; P ϭ 0.58) following treatment (12) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Individuals were administered ivermectin (100 g/kg) and albendazole (400 mg) as described previously (12). Posttreatment ex vivo assessments were performed 8 months after the first drug administration (Table 1).…”
Section: Study Population (I) Pretreatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Co-infection, as in the patient described in this report, with the pathogen Onchoceriasis volvulus is commonly described with W. Bancrofti infection. This fact changes the treatment profile dramatically as DEC treatment can Onchoceriasis has resulted in severe allergic-type reactions [10]. As illustrated by this case, the complexities involved in treating parasitic infections demand a multidisciplinary approach with involvement of an infectious disease specialist as well as other specialties, such as opthamology, as necessary.…”
Section: Discussionmentioning
confidence: 99%